Evaluación técnico-financiera de la inyección continua solvente-polímero mediante simulación numérica para un área piloto del Campo Chichimene (2017)
The Chichimene Field is located in the Llanos Orientales Basin, and is operated by Ecopetrol S.A., in this project was studied the San Fernando’s Formation. (9 ° API) and with high viscosities (2000cp) with the purpose of increasing oil production, recovery factor and more incomes. The study focused on the middle of a compilation of information from the Chichimene field area, followed by a description of the recovery methods, where the solvent and polymer injection processes are specified, then the simulation model created with its different properties, which required the inclusion of virtual wells to achieve their respective historical adjustment.